Praktik Pencantuman Harga Dengan Pecahan Rupiah Sen Pada Jual Beli Online Perspektif Marketing Syariah (Studi kasus pada platform Tik Tok Shop Toko @R2VariasiMotor2 dan Affiliator @Showcaseauliaivya) - Rayodin, Habib; Islami, Trinah Asi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The increasing prevalence of online commerce via digital platforms such as TikTok Shop has introduced a trend wherein product prices are displayed using fractional rupiah values, such as Rp10,568 or Rp25,723. This emerging practice has prompted ethical and Islamic legal scrutiny, particularly since the use of cent denominations is no longer common in everyday transactions in Indonesia. This study aims to examine how such pricing practices are implemented by sellers on TikTok Shop and whether they align with the principles of sharia-compliant marketing. This research is grounded in the theoretical framework of Sharia Marketing, which emphasizes four core values: monotheism (tauhid), justice (equilibrium), responsible freedom (free will), and accountability (fardh). The analysis also incorporates the concept of the sharia marketing mix, with particular attention to the pricing component, to assess the religious validity of using fractional pricing in digital marketplaces. A qualitative case study approach was employed for this research. Data were obtained through semi-structured interviews with two TikTok Shop participants: the seller @R2VARIASIMOTOR2 and the affiliate marketer @Showcaseauliaivya. These interviews were conducted to explore their motivations, rationales, and the perceived impact of employing fractional pricing in their business transactions. The findings indicate that both participants adopted fractional pricing either as a deliberate marketing strategy or as a default output of the TikTok Shop’s automated pricing system, with no intent to deceive customers. Final transaction amounts are rounded at the point of purchase, ensuring no financial harm to the buyer. From a sharia marketing standpoint, this pricing approach remains acceptable provided it avoids elements of deceit (gharar), is conducted transparently, and is rooted in sincere intent. Consequently, the use of fractional rupiah pricing on TikTok Shop may be regarded as permissible under Islamic commercial ethics, so long as it adheres to the principles of honesty, clarity, and equity in transactions.